HUBUNGAN SELF-EFFICACY TERHADAP KECEMASAN MAHASISWA KEPERAWATAN MENGHADAPI UJIAN PRAKTIK LABORATORIUM - Ni Komang Ayu Eka Jayanti; Komang Menik Sri Krisnawati; Ni Luh Putu Shinta Devi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
One form of learning in the PSSKPN is the laboratorium practice. When the Student facing laboratory practice exams, they would experience various conditions such as, anxiety, fear, panic, and imagining how the exam would be causes anxiety to students. Self-efficacy is an effort to prevent anxiety. The purpose of this study was to determine the relationship between self-efficacy with anxiety in nursing students when facing laboratory practice exams. This research was a correlative descriptive study with data collection methods that used a retrospective approach. The sample consisted of 61 respondents obtained by the total sampling technique. The research instrument on self-efficacy used General of self-efficacy (GSE) and instruments on anxiety used Zung self-rating anxiety scale (ZSAS). Data analysis was used Spearman rank correlation test. The results of this study showed that there is a significant relationship between self-efficacy and anxiety. The correlation was negative relations and moderate strength (p <0.05; rs = - 0.0443) which means that the higher the self-efficacy the lower anxiety is felt. The researcher suggested that there should increase in self-efficacy in nursing students to reduce anxiety when facing laboratory practice exams. Keywords: Anxiety, Self-Efficacy, Laboratory Practice Exam